2012
DOI: 10.1016/j.biochi.2012.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a series of 4-aminoquinolines that stimulate caspase-7 mediated cleavage of TDP-43 and inhibit its function

Abstract: Dysfunction of the heterogeneous ribonucleoprotein TAR DNA binding protein 43 (TDP-43) is associated with neurodegeneration in diseases such as amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). Here we examine the effects of a series of 4-aminoquinolines with affinity for TDP-43 upon caspase-7-induced cleavage of TDP-43 and TDP-43 cellular function. These compounds were mixed inhibitors of biotinylated TG6 binding to TDP-43, binding to both free and occupied TDP-43. Incubation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…37 While we observed a substantial decrease in affinity for nucleic acids for TDP-43 upon UBQLN2 binding, the affinity of AAQ1 for TDP-43 was much less effected, being only 5-fold less potent for inhibition of UBQLN2 binding to TDP-43 compared to inhibition of nucleic acid binding to TDP-43. Further characterization of AAQ1 mediated inhibition of UBQLN2 binding indicated that AAQ1 was competitive with UBQLN2 binding, therefore suggesting that AAQ1 also binds to the C-terminal region of TDP-43.…”
Section: 0 Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…37 While we observed a substantial decrease in affinity for nucleic acids for TDP-43 upon UBQLN2 binding, the affinity of AAQ1 for TDP-43 was much less effected, being only 5-fold less potent for inhibition of UBQLN2 binding to TDP-43 compared to inhibition of nucleic acid binding to TDP-43. Further characterization of AAQ1 mediated inhibition of UBQLN2 binding indicated that AAQ1 was competitive with UBQLN2 binding, therefore suggesting that AAQ1 also binds to the C-terminal region of TDP-43.…”
Section: 0 Discussionmentioning
confidence: 55%
“…Based on this biochemical assay using HTRF technology, UBQLN2 binds to both full length and a C-terminal fragment of TDP-43 (261-414 aa) with similar affinities, but not N-terminal TDP-43 (1-260 aa), suggesting that UBQLN2 interacts with TDP-43 at the C-terminus. Single stranded DNA oligonucleotides and 4-aminoquinolines which bind to TDP-43 37 , also inhibit UBQLN2 binding to TDP-43 with similar rank order affinities. Inhibitor characterization experiments demonstrated that the TDP-43 oligonucleotide TG12 and UBQLN2 interact noncompetitively with TDP-43, thereby supporting the hypothesis that UBQLN2 interacts with TDP-43 at a site distinct from oligonucleotide binding.…”
Section: 0 Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While caspase-3 is thought to be the major caspase for the cleavage of TDP-43, caspase 7 may be also involved as reported previously (Zhang et al, 2007;Cassel et al, 2012). Our experiment did not specify exactly which protease is the executer.…”
Section: Discussionmentioning
confidence: 71%